Threats, weaknesses and limitations of the surgery based on the evidence - Vojvodic Hernandez, Ivan (2024)
The evidence based surgery is sustained by clínical investigations and in the positivism. Both theories are being questioning by its own surgical practice and its own characters in which the technique and art reflects its main purpose. In consequence there is not enough number of published evidence. This constituted a limitation on the application of the CBE. This purpose of this article is to view the treads, weakness and limitations of the CBE.